Access to Leadership Positions and Career Trajectories among Georgian and American Women in the Twentieth and Twenty-First Centuries - Tcharbadze, Salome; Shioshvili, Tamar (European Scientific Journal, ESJ, 2026)
This article examines how institutional, organizational, and care-related factors shape women’s access to leadership positions and career trajectories in Georgia and the United States. Its objective is to identify the principal mechanisms that facilitate or constrain women’s progression from education and labour-market entry to managerial and senior leadership positions and to compare how these mechanisms operate across two distinct national contexts. The study uses a qualitative comparative literature review and policy analysis. It primarily draws on peer-reviewed research, official statistics, and institutional reports published between 2020 and 2026, while selected foundational theoretical works and historical evidence are used to contextualize developments across the twentieth and twenty-first centuries. The analysis is organized around five interrelated dimensions: organizational culture and promotion practices, caregiving responsibilities, flexible work arrangements, intersectional inequalities, and structural access to career-development opportunities. The findings indicate that women’s limited representation in leadership cannot be explained by insufficient qualifications or ambition. In the United States, measurable progress in senior leadership coexists with persistent barriers at the first promotion into management, unequal access to sponsorship, motherhood-related penalties, and racialized inequalities. In Georgia, formal gender equality and high levels of female educational participation coexist with unpaid care burdens, occupational segregation, regional disparities, limited care infrastructure, and enduring patriarchal expectations. Across both contexts, flexible and hybrid work may support employment continuity, but they may also weaken visibility, sponsorship, and promotion opportunities when performance evaluation and career-development systems are not transparent. The article concludes that sustainable leadership equality requires institutional reforms, including transparent promotion criteria, accessible care services, gender-responsive labour policies, sponsorship systems, pay transparency, and protection against flexibility-related stigma.